The Case of Local Administration in Turkey Within the Perspective of Participatory Democracy - Tanzer Celikturk; Yavuz Ramazan Kus (European Scientific Journal, ESJ, 2017)
Today, democracy and local governments are emerging as concepts that are handled together. There is widespread belief that local governments, which meet the socioeconomic and cultural needs of the individuals in the local community and provide public goods and services at the local level, are the basic institutions of democratic organization. With Turkey becoming the candidate country of the European Union in 1999 and the beginning of full membership negotiations in 2005, legal changes that will strengthen the local autonomy have accelerated. Local democracy does not even settle in Turkey, apart from the weakness of local governments and local autonomy. Although Turkey has signed the 'European Charter of Local Self-Government' in the EU harmonization process, it is clear that local democracy and local autonomy can not develop at the point where local awareness does not exist, although various policies are under the local government reform.